Effect of calcination temperature on the performance of K-Co/Al2O3 catalyst for oxidative coupling of methane - Sarannuch Sringam; Thongthai Witoon; Chularat Wattanakit; Waleeporn Donphai; Metta Chareonpanich; Günther Rupprechter; Anusorn Seubsai (Carbon Resources Conversion)
The oxidative coupling of methane (OCM) involves directly converting methane to C2+ hydrocarbons (such as ethylene and ethane) via a reaction with oxygen. This study elucidated the effect of the calcination temperature on the structure and catalytic performance of potassium-doped-cobalt oxide supported on an alumina (K-Co/Al2O3) catalyst for the OCM reaction. The catalyst was highly active at relatively low reactor temperatures (500–640 °C). Four calcination temperatures (400, 500, 600, and 700 °C) were investigated, with the results showing that the calcination temperature strongly affected catalytic properties, such as the crystalline phases, elemental distribution, physical properties, and catalytic basicity, leading to a wide range in catalytic performances. The catalyst calcined at 400 °C was superior among the catalysts, with 8.3 % C2+ yield, 24.8 % C2+ selectivity, and 33.6 % CH4 conversion at 640 °C. Furthermore, the catalyst was robust over 24 h of testing.